New rapid detection by using a constant temperature method for avian leukosis viruses - Wu, Xiuhong; Chu, Fengsheng; Zhang, Luxuan; Chen, Sheng; Gao, Liguo; Zhang, Hao; Huang, Haohua; Wang, Jin; Chen, Mengjun; Xie, Zi; Chen, Feng; Zhang, Xinheng; et al. (Frontiers in Microbiology, 2022)
The avian leukemia virus causes avian leukemia (AL), a severe immunosuppressive disease in chickens (ALV). Since the 1990s, the diversity of ALV subpopulations caused by ALV genome variation and recombination, and the complexity of infection and transmission, currently no effective commercial vaccine and therapeutic for ALV, has resulted in severe economic losses to the chicken business in various parts of the world. Therefore, as a key means of prevention and control, an effective, rapid, and accurate detection method is imperative. A new real-time reverse-transcription recombinase-aided amplification (RT-RAA) assay for ALV with rapid, highly specific, low cost, and simple operational characteristics have been developed here. Based on the amplification of 114 base pairs from the ALV P12 gene, real-time RT-RAA primers and a probe were designed for this study. The lowest detection line was 10 copies of ALV RNA molecules per response, which could be carried out at 39 ℃ in as fastest as 5 minutes and completed in 30 minutes, with no cross-reactivity with Marek's disease virus, avian reticuloendothelial virus, Newcastle disease virus, infectious bronchitis virus, infectious bursal disease virus, infectious laryngotracheitis virus, and avian influenza virus. Furthermore, the kappa value of 0.91 (>0.81) was compared with reverse transcription-polymerase chain reaction (RT-PCR) for 44 clinical samples, and the coefficients of variation were within 5.18% of the repeated assays with three low-level concentration gradients. These results indicate that using a real-time RT-RAA assay to detect ALV could be a valuable method.